Preparation and properties of highly conductive palmitic acid/graphene oxide composites as thermal energy storage materials - Mehrali M.; Latibari S.T.; Mehrali M.; Indra Mahlia T.M.; Cornelis Metselaar H.S. (Elsevier Ltd, 2023)
PA/GO (palmitic acid/graphene oxide) as PCMs (phase change materials) prepared by vacuum impregnation method, have high thermal conductivity. The GO (graphene oxide) composite was used as supporting material to improve thermal conductivity and shape stabilization of composite PCM (phase change material). SEM (Scanning electronic microscope), FT-IR (Fourier transformation infrared spectroscope) and XRD (X-ray diffractometer) were applied to determine microstructure, chemical structure and crystalloid phase of palmitic acid/GO composites, respectively. DSC (Differential scanning calorimeter) test was done to investigate thermal properties which include melting and solidifying temperatures and latent heat. FT-IR analysis represented that the composite instruction of porous palmitic acid and GO were physical. The temperatures of melting, freezing and latent heats of the composite measured through DSC analysis were 60.45, 60.05C, 101.23 and 101.49kJ/kg, respectively. Thermal cycling test showed that the form-stable composite PCM has good thermal reliability and chemical stability. Thermal conductivity of the composite PCM was improved by more than three times from 0.21 to 1.02. As a result, due to their acceptable thermal properties, good thermal reliability, chemical stability and great thermal conductivities, we can consider the prepared form-stable composites as highly conductive PCMs for thermal energy storage applications. 2013 Elsevier Ltd.